Sosialisasi Akuntansi dan Perpajakan Bagi UMKM di Kelurahan Rancamaya, Bogor - Luh Nadi; Harry Barli; Thom Deutmar Londo Doaly (Universitas Pamulang, 2022)
We have carried out PKM odd semester 2022/2023 in Rancamaya Village, South Bogor District, Bogor. The theme of this PKM activity is